Evaluation of the effectiveness and safety of anti-obesity drugs - an update on the current state of knowledge on available and investigational drugs - Cichoń, Katarzyna; Chyćko, Małgorzata; Czarnota, Julia; Kromer, Agata; Zapała, Magdalena Alicja; Środoń, Agnieszka; Wilk, Joanna; Cholewa, Małgorzata Maria; Gawryś, Agnieszka; Łapaj, Monika (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work: Disturbing epidemiological data indicate that obesity has become a global problem and has reached the size of a worldwide epidemic. The search for effective methods of combating obesity seems to be an important step in preventing cardiovascular diseases and numerous metabolic complications. The aim of the study is to assess the effectiveness and safety of available drugs used in the treatment of obesity in accordance with the current state of knowledge and to present new pharmacological options. State of knowledge: Pharmacotherapy provides overweight and obese adults with the opportunity to support weight reduction in the event of failure of lifestyle modifications. Currently registered drugs for the treatment of obesity are orlistat, lorcaserin, liraglutide and combination preparations: phentermine/topiramate and naltrexone SR/bupropion SR. Summary: Among the currently available drugs for obesity, the most effective are phentermine/topiramate and liraglutide. Research is also underway on the use of new substances that promote weight loss. The latest data on semaglutide and tirzepatide have better efficacy results compared to currently available drugs with a similar safety profile. The latest data on semaglutide and tirzepatide improve the efficacy results of current drugs while maintaining a similar safety profile. It seems that the best way to lose excessive body weight should be an individualized approach to the treatment of obesity among patients, taking into account i.a. degree of obesity, comorbidities, contraindications, patient preferences, cost and availability of treatment. In clinical practice, when choosing a drug, we should pay attention to side effects and find a balance between effectiveness and safety. In addition to weight loss, the use of anti-obesity drugs has many additional benefits, including improvement of the cardiometabolic profile, reduction of glucose, insulin and lipids in the blood.